Science and Technology in Ecuador. A Retrospective Look into the Future - Danny Zambrano-Vera, Danny (2019)
In the last decade, Ecuador present changes in the structure and functioning of the National System of Higher Education, referring specifically to the deployment of projects in science, research and development, such as Prometheus Program, Ingenious Program, Graduate and Postgraduate Scholarships in national and foreign universities, construction of four emblematic universities, among other innovation and technology initiatives. The efforts of the National Government in this period were diverse for the implementation of social ideas in higher education, however, the results showed a biased system, bureaucratized and without guidelines in the creation of value and synergies among the different participating actors. The purpose of this study is to prepare a diagnostic the situation of the National System of Higher Education of Ecuador in those aspects related to research and development, science and technology, period 2012-2014. To this end, the National Survey of Science, Technology and Innovation Activities (ACTI) was used as an analytical tool, which results are exposed from the use of descriptive statistical techniques, managing to see that the incremental allocation of resources for higher education did not allow to articulate of a public policy of social transformation, moreover, when the rendering of accounts reveals the dissatisfaction among its actors, widens the gap between society and knowledge.